2014
DOI: 10.1017/s0021859614000999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and association among factors influencing storage root bulking in cassava

Abstract: Cassava (Manihot esculenta Crantz) is an important storage root crop with largely unexplored and unexplained potentially valuable genetic variability. Genetic variability is important in selecting suitable genotypes for crop improvement. The present study was aimed at assessing the extent of variability in cassava storage root bulking, based on fresh storage root yield accumulated over time. Twelve cassava genotypes were evaluated in a randomized complete block design at three contrasting locations in Uganda. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…On the other hand, the lowest RY was observed for genotypes 1 (16.63 t ha -1 ) and 12 (15.38 t ha -1 ). Previous studies also observed a positive correlation between RY and number of roots per plant (Rós and São João 2016, Tumuhimbise et al 2015.…”
Section: Morphoagronomic Characterizationsupporting
confidence: 52%
“…On the other hand, the lowest RY was observed for genotypes 1 (16.63 t ha -1 ) and 12 (15.38 t ha -1 ). Previous studies also observed a positive correlation between RY and number of roots per plant (Rós and São João 2016, Tumuhimbise et al 2015.…”
Section: Morphoagronomic Characterizationsupporting
confidence: 52%
“…However, there was no significant difference for NRRP and FRY. Genetic variation for cassava root traits, including root yield, has been commonly identified in different studies in Brazil (Barreto & Resende, 2010;Oliveira et al, 2014Oliveira et al, , 2015 and in Africa (Aina et al, 2007;Ojulong et al, 2008;Tumuhimbise et al, 2015). Possibly, in the present study, the augmented blocks design was not suitable to detect differences for root yield.…”
Section: Resultsmentioning
confidence: 66%
“…There were positive and significant correlations between PSW and NRP, PSW and FRY, and FRY and NRP (Table 3). These positive and significant correlations were expected, since the increase in root yield has been associated with plant shoot growth and with the increase in the number of roots (Elias et al, 2001;Tumuhimbise et al, 2015). However, a negative and significant correlation was verified between FRY and NRRP, which was also expected, since root rot leads to yield loss.…”
Section: Resultsmentioning
confidence: 77%
“…Means were separated using least significance differences at 5% significance level. The following mixed model, with genotype declared as fixed effects and locations and harvest times as random effects, was used (Tumuhimbise et al 2014) (Equation (2)):…”
Section: Discussionmentioning
confidence: 99%